The curse of knowledge increases self-selection into competition: Experimental evidence - David Danz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The psychology literature provides ample evidence that people have difficulties taking the perspective of less informed others. This paper presents a controlled experiment showing that this "curse of knowledge" can cause comparative overconfidence and overentry into competition. In a broader context, the results provide an explanation for the overconfidence of nascent entrepreneurs and the substantial rate of failure among new businesses.
Keywords: C91; D80; D82; D83; D84; 330; curse of knowledge; hindsight bias; information projection; overconfidence; sorting; incentive schemes; competition; beliefs; experiments